Primary adenosquamous carcinoma of the stomach - Suguna Venugopal Belur; Hemalata Mahantappa (Archives of Clinical and Experimental Surgery, 2017)
Adenosqamous carcinoma of the stomach is a rare subtype, accounting for less than 0.4 % of cases of gastric cancer. It is aggressive and tends to be present in advanced stages with a worse prognosis than typical gastric adenocarcinoma. This case is interesting because of its rarity and histogenesis. Based on the fact that clinically and endoscopically, it resembles intestinal-type adenocarcinoma, histopathology is required to make definitive diagnosis. Presented here is a case report of a 70-year-old male that presented with the features of gastric outlet obstruction. Distal gastrectomy with D1duodenectomy showed adenosquamous carcinoma at the distal end of the stomach with metastatic deposits in 4/6 perigastric lymphnodes. With immunohistochemistry, the squamous component demonstrated CK5/6 positivity and the adenocarinoma component was positive for CK7. [Arch Clin Exp Surg 2017; 6(4.000): 217-220]